A Comparative Study of the Therapeutic Education System for Incarcerated Substance-Abusing Offenders. (June 2016) - Chaple, Michael; Sacks, Stanley; McKendrick, Karen; Marsch, Lisa A.; Belenko, Steven; Leukefeld, Carl; Prendergast, Michael; French, Michael
Although many efficacious and cost-effective treatments have been established, very few substance-abusing offenders receive such treatment while incarcerated. This study compares the effectiveness of a computerized intervention, the Therapeutic Education System (TES), with Standard Care on measures of crime (including re-incarceration), drug use, and HIV risk behavior post prison release. Results show that TES and standard treatment were equally effective in reducing criminality, relapse to drug use, and HIV risk behavior. In prisons, where a majority of substance-using offenders do not receive treatment, identifying an equally effective high-volume alternative such as TES can greatly expand access to quality psychosocial interventions.